2017
DOI: 10.1080/10245332.2017.1354428
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability and Promoter Hypermethylation of DNA repair genes in Hematologic Malignancies: a forthcoming direction toward diagnostics

Abstract: The presence of specific microsatellite marker hyper-mutability and consistent promoter hypermethylation in leukemia or lymphoma can be considered as a part of routine diagnostic test in clinical laboratories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Research shows that MMR ensures replication fidelity by correcting mismatches generated during DNA replication 37, 38. DNA MMR and direct reversal of damage (DRD) are two repair mechanisms that help in the removal of faulty base pairs and alkyl adduct formation, respectively, to avoid long-term effects of toxicity, tumorigenesis, and mutagenesis 39 …”
Section: Discussionmentioning
confidence: 99%
“…Research shows that MMR ensures replication fidelity by correcting mismatches generated during DNA replication 37, 38. DNA MMR and direct reversal of damage (DRD) are two repair mechanisms that help in the removal of faulty base pairs and alkyl adduct formation, respectively, to avoid long-term effects of toxicity, tumorigenesis, and mutagenesis 39 …”
Section: Discussionmentioning
confidence: 99%
“…Valdez et al [146] have recently shown that the combined use of HMA, HDACi, and PARPi resulted in extensive DNA damage, double-strand breaks (DSBs), and apoptosis. Furthermore, evidence is accumulating that links the microsatellite instability (MSI) phenotype of hematological tumors to the disruption of the mismatch repair pathway by promoter hypermethylation of the pathway's own genes [147]. Thus, it is reasonable to speculate further that, as observed in solid tumors, the MSI phenotype might confer some hematological neoplasms with higher rates of ICI responses, through enhancement of neoantigen presentation [148].…”
Section: Discussionmentioning
confidence: 99%
“…Several repair genes ( MSH2, MSH3, MSH6, MLH1, MLH3, PMS1 and PMS2 ) are involved in this process and work by forming heterodimers. The interaction between mismatch recognition complexes and other proteins such as helicase, proliferating cell nuclear antigen, replication protein A, exonuclease 1 is required for the rectification of base-pair alterations, insertion-deletion loops and hetero-duplexes instigated during replication and recombination (9). MMR genes aberrations can be investigated by immunohistochemistry (IHC) for MMR proteins, which is a quick and simple assay to recognize MMR status (1012).…”
Section: Introductionmentioning
confidence: 99%